ANALISIS FATWA TARJIH MUHAMMADIYAH TENTANG ISTRI IKUT ORGANISASI DITINJAU DARI SADDU DZARI’AH DAN DAMPAKNYA TERHADAP KELUARGA - Putra, Fajriman; Azwar, Zainal (USRAH: Jurnal Hukum Keluarga Islam, 2025)
This study adopts a qualitative method with a literature review approach. The aim of this research is to understand the istinbath (derivation) method used by the Muhammadiyah Tarjih Council in issuing fatwas related to women’s participation in organizations. The findings of this study indicate that the Muhammadiyah Tarjih Council refers to the Qur'an and Hadith to explain the wife’s duties towards her husband, children, and parents, as well as guidelines regarding congregational prayer and women’s participation in organizations. In this context, women may participate in religious organizations if it brings benefit, but the impact on family harmony must be considered. The principle of Sadd al-Dzari'ah is applied to prevent negative consequences arising from the conflict between organizational and family interests, prioritizing based on urgency and maintaining a balance between both interests. Keywords:  Tarjih Fatwa; Wife Organization; Sadd al-Dzari'ah